Riding into the future : a financial examination of SoulCycle and the indoor cycling studio trend - Hambrick, Marion E. (London : Human Kinetics, Inc., 2017)
SoulCycle is a $122 million company offering customers 45-min workouts in its indoor cycling studios. As one of the first boutique fitness firms to emerge in the $28.5 billion fitness industry, SoulCycle grew from one indoor cycling studio in New York City in 2006 to 67 studios across the United States by 2016. SoulCycle executives faced a pivotal moment in May 2016. Chief executive officer Melanie Whelan recognized the company faced increasing competition in the boutique fitness segment, with companies such as Flywheel and Peloton making inroads into this market. In addition, two of SoulCycle's founders resigned from their leadership positions earlier the same year. These developments led to questions about the long-term viability of SoulCycle within the larger fitness industry. A detailed financial analysis of SoulCycle, including an examination of the company's financial statements, financial ratios, strategic initiatives, and competitors, could provide insights about its chances for continued success.
Originally Published InHambrick, M. (2017). Riding into the future: A financial examination of SoulCycle and the indoor cycling studio trend. Case Studies in Sport Management, 6(1), 86-94.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Whelan, Melanie; SoulCycle; Physical fitness centers -- United States; Spinning (Trademark); Corporations -- Finance; Competition